Temporal lobectomy for intractable complex partial seizures in pediatric patients - Pongsakdi Visudhiphan (2018)
Fourteen children, 7 boys and 7 girls, who failed conventional medical treatment for complex partial seizures underwent anterior temporal lobectomy at Ramathibodi Hospital, Bangkok, Thailand, from July 1993 to June 1998. The mean age at onset of patients was 6.7 years old and the mean duration of seizures before surgery was 6.4 years. The age of patients at surgery ranged from 8 to 22 years old. These patients had had limited presurgical evaluation which included video-electroencephalography (EEG), magnetic resonance imaging (MRI) and single photon emission computed tomography (SPECT). All patients demonstrated concordant among clinical symptoms, EEG, MRI and SPECT on the same side of the temporal lobe. Ten and 4 patients had unilateral and bilateral temporal lobe lesions respectively. The operations were done on the left in 10 patients and on the right in 4 patients. Seizure free after 1/2 - 5 years of follow-up was obtained in 70 per cent of patients which included 9 of 10 patients with unilateral temporal lesion and 1 of 4 patients with bilateral temporal lesions. The rest of the patients showed marked reduction of seizures except for one patient with bilateral lesions in whom only 50-70 per cent reduction was obtained. Marked improvement of behaviour was also observed in 70 per cent of patients. Resected brain specimens revealed mesial temporal sclerosis, gliosis, tumors and cavernoma in 6, 5, 2 and 1 patients respectively.